Cover Feature: Non‐Planar Structures of Sterically Overcrowded Trialkylamines (Chem. Eur. J. 11/2021). Issue 11 (23rd December 2020) - Banert, Klaus; Heck, Manuel; Ihle, Andreas; Shoker, Tharallah; Wörle, Michael; Boese, A. Daniel
Abstract : Even record‐breaking steric stress cannot enforce complete planarization of the nitrogen atom in trialkylamines. This is demonstrated for several examples with the aid of single‐crystal X‐ray diffraction studies. Moreover, quantum chemical calculations generate the precise gas‐phase structures of the sterically overcrowded tertiary amines showing heights of the NC3 pyramids and preferred molecular conformers, which are similar to those resulting from the X‐ray analysis. More information can be found in the Full Paper by K. Banert, M. Wörle, A. D. Boese, et al. on page 3700 .